2021
DOI: 10.1093/infdis/jiab097
|View full text |Cite
|
Sign up to set email alerts
|

Viral Load of Severe Acute Respiratory Syndrome Coronavirus 2 in Adults During the First and Second Wave of Coronavirus Disease 2019 Pandemic in Houston, Texas: The Potential of the Superspreader

Abstract: Background During the COVID-19 pandemic, a minority of index cases are associated with a majority of secondary cases suggesting that super-spreaders could drive the pandemic. We identified a phenotype in individuals with extremely high viral load who could act as super-spreaders. Methods Data were analyzed from individuals tested for SARS-CoV-2 from March 18 through August 15, 2020. Outcomes were compared using contingency ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(51 citation statements)
references
References 32 publications
5
46
0
Order By: Relevance
“…Most patients infected with SARS-CoV-2 elicit robust antibody responses to both the S and N proteins [64][65][66], though the significance of timing and strength of those responses to predicting clinical outcome remains unclear [52,53,67]. Here, we likewise observed that a majority of participants developed antibodies to both the N and S protein, usually within two weeks of symptom onset.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…Most patients infected with SARS-CoV-2 elicit robust antibody responses to both the S and N proteins [64][65][66], though the significance of timing and strength of those responses to predicting clinical outcome remains unclear [52,53,67]. Here, we likewise observed that a majority of participants developed antibodies to both the N and S protein, usually within two weeks of symptom onset.…”
Section: Discussionsupporting
confidence: 55%
“…De novo prediction of a patient's risk of severe COVID-19 and poor outcome remains imprecise, despite the identification of several independently associated factors, including: demographic factors, such as age and sex [1], clinical factors, such as BMI, known co-morbidities, and respiratory rate [9,58], virological factors, such as viral load and viral genotype [53]; and serological factors, such as inflammatory markers, antibody responses, and autoimmune complications [59,60]. A number of composite measures of patient deterioration have likewise been developed to assist with clinical management of disease, but no one measure is utilized consistently across disparate health systems [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although sensitivity is less than 10% in samples with a low viral load, it reaches 100% with a viral load of more than 10 8 SARS-CoV-2 RNA copies per ml. As the latter defines potential super-spreaders, it is crucial to identify those individuals as quickly as possible to prevent hospital outbreaks [22] . The low sensitivity of RDT in persons with low viral loads means these tests must be combined with RT-qPCR.…”
Section: Discussionmentioning
confidence: 99%
“…The study shows that extremely high viral load was observed in majority of patients and the patient with extremely high viral load show median duration of viral shedding which varies from 25-28days .Viral load is based on RT-PCR CT value :extremely high <16, high:16-21,medium:21-31,low:40 This data supports that individual with high viral load are potential superspreaders for SARS COV-2 and major drivers of pandemic waves. 9 More and more families,with all or most of the family members, were getting infected. The exponential increase in cases in 2 nd wave is attributed to high transmissibility of virus.During the first wave, infected population was upto 50% from urban areas, the 2 nd wave seem to be spreading more to rural areas.. (9) A combination of a large asymptomatic population and the presence of more infectious variants of virus and decreased strictness along with lesser monitoring in the containment zones as compared to last year, virus got transmitted even to those who were staying indoors and also because the asymptomatic people did not isolate themselves in a home setting .…”
Section: Why Transmission Is High?mentioning
confidence: 99%

Mysterious Covid 2nd Wave in India

Ritu Kaushik,
Deeksha Chaudhary,
Rajpal Verma
et al. 2021
IJOCM